Jejak-Jejak Sikap Bakti Konfusianisme (Xiao 孝) dalam Praktik Penghormatan Leluhur Etnis Tionghoa di Indonesia - Hadiwijaya, Kristian (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2025)
Ancestor veneration is a deeply rooted tradition in Chinese culture and is closely linked to Confucian values, particularly the concept of xiao (filial piety). This article aims to analyze how Confucian values, particularly filial piety, are manifested in the practice of ancestor veneration among Chinese in Indonesia. The results show that the practice of ancestor veneration reflects the principle of xiao in the form of appreciation for ancestral services, intergenerational moral obligations, and family harmony. This study strengthens the theory that Confucian philosophy is not merely an abstract philosophy, but is truly lived in everyday cultural practices as a life value. This research also contributes to understanding the dynamics of Chinese tradition and the relevance of Confucian values in the modern context.